2021
DOI: 10.1159/000512105
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Thrombolysis Is Associated with Less Disabling Stroke and Lower Mortality in Multiple-Pass Endovascular Thrombectomy

Abstract: <b><i>Background and Purpose:</i></b> The benefit of bridging intravenous thrombolysis (IVT) in acute ischaemic stroke patients eligible for endovascular thrombectomy (EVT) is unclear. This may be particularly relevant where reperfusion is achieved with multiple thrombectomy passes. We aimed to determine the benefit of bridging IVT in first and multiple-pass patients undergoing EVT ≤6 h from stroke onset to groin puncture. <b><i>Methods:</i></b> We compared 90-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Subsequent meta-analyses including observational data provided inconclusive results regarding outcomes and treatment complications [ 57 , 58 , 59 , 60 , 61 , 62 ]. However, in the case of multiple passages, IVT appears to be associated with less disability and a smaller overall stroke volume [ 63 ]. The Multicenter Randomized Clinical trial of Endovascular treatment for Acute ischemic stroke in the Netherlands (MR CLEAN)-NO IV study showed neither non-inferiority (NIM 0.8; 0.84 [0.62–1.15]) nor superiority of direct MT [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent meta-analyses including observational data provided inconclusive results regarding outcomes and treatment complications [ 57 , 58 , 59 , 60 , 61 , 62 ]. However, in the case of multiple passages, IVT appears to be associated with less disability and a smaller overall stroke volume [ 63 ]. The Multicenter Randomized Clinical trial of Endovascular treatment for Acute ischemic stroke in the Netherlands (MR CLEAN)-NO IV study showed neither non-inferiority (NIM 0.8; 0.84 [0.62–1.15]) nor superiority of direct MT [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies discussed the effect of BT (bridging therapy: combined I.V. thrombolysis and mechanical thrombectomy) on FPE and clinical outcomes 3 , 4 . Neurologists and Neuro-interventionalists started to ask a question about the best pathway for AIS (Acute Ischemic Stroke), if BT or dMT (direct Mechanical Thrombectomy) is more beneficial to the outcome of patients and our health care system.…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al in a meta-analysis reported that FPE was associated with favorable 90-day outcomes with less morbidity without any effect of IVT between cases with FPE or without3 . Blair et al reported in a retrospective study that patients with FPE who received IVT had no benefit as regards clinical outcome in comparison with patients with multiple passes and received IVT4 . That might be due to the thrombolysis effect of alteplase on distal infarctions due to fragmentation of the thrombus after multiple trials of thrombectomy.Li et al reported in a meta-analysis a better 90-day favorable outcome in BT than dMT which is contradictory to our study…”
mentioning
confidence: 99%
“…Studies advocating BT claimed that, when preceding IVT, a bridging approach could accelerate the endovascular process and achieve successful recanalization by partially cracking and fragmenting the clot, not directly accessible by thrombectomy devices. [ 5 ] Other studies recommending d-MT noted several problems in such studies, including bias in individual selection and exclusion, cost issues, and delays in treatment time from symptom onset due to the nature of BT in terms of mixing and infusion. [ 2 ] We considered all these confounding factors and pooled our results with adjusted analysis, showing that BT and d-MT have similar therapeutic outcomes.…”
mentioning
confidence: 99%